Phylogenetically typing bacterial strains from partial SNP genotypes observed from direct sequencing of clinical specimen metagenomic data. Issue 1 (December 2015) - Sahl, Jason; Schupp, James; Rasko, David; Colman, Rebecca; Foster, Jeffrey; Keim, Paul
Abstract We describe an approach for genotyping bacterial strains from low coverage genome datasets, including metagenomic data from complex samples. Sequence reads from unknown samples are aligned to a reference genome where the allele states of known SNPs are determined. The Whole Genome Focused Array SNP Typing (WG-FAST ) pipeline can identify unknown strains with much less read data than is needed for genome assembly. To testWG-FAST, we resampled SNPs from real samples to understand the relationship between low coverage metagenomic data and accurate phylogenetic placement.WG-FAST can be downloaded fromhttps://github.com/jasonsahl/wgfast .